Exploring the Role of Mitochondria in Alzheimer with Network Pharmacology: A Bioinformatics Analysis - Riena, Nadya Ratna; Novalina, Fellen; Heng, Kahtleen Riani (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease marked by the pathological accumulation of beta-amyloid peptide and hyperphosphorylated tau. Growing body of evidence indicates that mitochondrial dysfunction plays a pivotal role in AD pathogenesis, by inducing neurotoxicity through the formation of oxidative stress and reactive oxygen species (ROS). This study aims to investigate relevant mitochondrial proteins in Alzheimer by employing network pharmacology. Protein-coding genes associated with AD were identified from the GeneCards database, extracting only genes scoring >1 in relevancy. Datasets associated with mitochondria were extracted from the STRING database. 621 overlapping proteins from both keywords were further enriched and topologically analyzed. This study employed enrichment analyses using ShinyGO to identify relevant biological, cellular, and molecular processes, in addition to disease pathways. Topology analyses were conducted through STRING and Cytoscape by implementing eight different centrality parameters and clustering, the genes were further curated to obtain pivotal proteins in AD and their dysregulation. Aligned with our enrichment analyses, the proteins topologically relevant were components of the mitochondrial oxidative phosphorylation (OXPHOS) pathway, crucial to the respiratory electron transport chain and ATP synthesis system. This study provides a foundation for the discovery of multi-target drugs in AD therapy.